Assessment of Angelica sinensis (Oliv.) Diels as a repellent for personal protection against mosquitoes under laboratory and field conditions in northern Thailand - Champakaew D. (2017)
© 2016 The Author(s). Background: Angelica sinensis (Oliv.) hexane extract (AHE) has been reported as a proven and impressive repellent against laboratory-reared female Aedes aegypti mosquitoes. With the aim of promoting products of plant origin as a viable alternative to conventional synthetic substances, this study was designed to transform AHE-based repellents for exploitable commercial production by enhancing their efficacy and assessing their physical and biological stability as well as repellency against mosquitoes under laboratory and field conditions. Methods: The chemical profile of AHE was analyzed by qualitative gas chromatography-mass spectrometry (GC-MS) technique. AHE was supplemented with vanillin, as a fixative, and then investigated for repellency and comparison to the standard synthetic repellent, DEET, under both laboratory and field conditions. Determination of physical and biological stability as a repellent was carried out after keeping AHE samples under varying temperatures and for different storage times. Results: GC-MS analysis revealed that AHE contained at least 21 phytochemical compounds, constituting 95.74 % of the total content, with the major constituent of 3-N-butylphthalide (66.67 %). Ethanolic formulations of AHE and DEET showed improvement of repellency in a dose-dependent manner when vanillin was added in laboratory assessment. While 5-25 % AHE alone provided median complete-protection times of 2.0-6.5 h against Ae. aegypti, these times were increased to 4.0-8.5 h with a combination of AHE and 5 % vanillin (AHEv). Protection times against Ae. aegypti were extended from 2.25 to 7.25 h to 4.25-8.25 h when 5-25 % DEET was combined with 5 % vanillin (DEETv). In determining stability, all stored AHE samples exhibited similar characteristics such as liquid phases with aromatic odor comparable to those of fresh preparations. Furthermore, repellent activity of stored AHE samples lasted for at least six months, with varied efficacy (4.5-10.0 h) against Ae. aegypti. Field trials revealed strong repellency from both 25 % AHEv and 25 % DEETv, with complete protection (100 %) against a wide range of local mosquito populations. A total of 5,718 adult female mosquitoes, with the most predominant being Culex quinquefasciatus (41.47 %), Armigeres subalbatus (41.13 %), and Culex vishnui (10.53 %), was collected during field applications. No local skin reaction or other allergic responses was observed during both laboratory and field study periods. Conclusions: Angelica sinensis proved to have not only impressive repellency against both laboratory Ae. aegypti and a wide range of natural mosquito populations, but also relative stability in physical and biological performance.